Association Between Major Depressive Disorder and Sleep Disturbances Through Inflammation in Adolescents - Reddy, Abhishek; Thootkur, Mounica; Li, Li (Frontiers in Psychiatry, 2020)
Background: Although approximately 13% of adolescents suffer from Major Depressive Disorder (MDD), and many adolescents have reported sleep disturbances, the relationship between sleep disturbances and MDD in adolescents is poorly understood. Thus, our objective was to study how adolescent MDD was related to sleep disturbances in a cross-sectional study, and the potential role of inflammation linking adolescent MDD to sleep disturbances. Methods: Ninety-two female and male, African American and White, adolescents aged 15-18 completed the study. Adolescents were diagnosed with MDD according to the Diagnostic and Statistical Manual of Mental Disorders-5 as confirmed by the MINI International Diagnostic Interview. The severity of depression was assessed using the Quick Inventory of Depressive Symptomatology. Sleep disturbance was measured using the Pediatric Sleep Questionnaires (PSQ). Blood sample was collected from each participant for measuring the inflammatory factors. Results: Compared with the controls (n=39), adolescents with MDD (n=53) had greater PSQ scores (0.32±0.02 vs. 0.10±0.02). In adolescents with MDD, PSQ scores were correlated with the severity of depressive symptoms (r=0.31, p<0.05). In addition, tumor necrosis factor-α levels were greatly elevated in the MDD group (2.4±0.1 vs. 1.8±0.1 pg/ml) compared with the controls. Severity of depressive symptoms was best predicted by PSQ scores, medications and childhood experiences. Conclusions: Sleep disturbance measured by the PSQ is associated with severe depressive symptoms in adolescents, and one potential pathway may be through elevated tumor necrosis factor-α. Further research is warranted to probe a cause and effect relationship among sleep disturbances, MDD and chronic inflammation.